Effect of high fat consumption on cell proliferation activity of colorectal mucosa and on soluble faecal bile acids. Issue 10 (October 1988) - Stadler, J; Stern, H S; Yeung, K S; McGuire, V; Furrer, R; Marcon, N; Bruce, W R
Abstract : To assess the effect of fat consumption on the proliferation of the rectal mucosa, 30 normal volunteers (22 to 71 years) were randomly allocated to three groups: (a) basal low fat diet containing 30 g of fat per day; (b) the basal diet with doses of 30 g corn oil taken with each of the three meals: 120 g fat/day; (c) the basal diet with one dose of 90 g corn oil after the last meal: 120 g fat/day. Rectal biopsies were taken 15 cm from the anal verge after five days on the diets and mucosal cell proliferation was measured by labelling index (LI). The LI was significantly (p less than 0.01) higher in group (c) (9.2) than in group (a) (5.9), with group (b) intermediate (6.8). In multiple stepwise regression analysis, the data were best fitted with age and the variable indicating fat consumed as a bolus as predictors of LI (r2 = 0.39, p less than 0.001). In separate analyses the regression coefficient with age in the fat bolus group was 0.23, p less than 0.001. There was some tendency towards lower bile acids in the faecal water in group (a) than in groups (b) and (c) following the diets and between the bile acids and LI (for lithocholic acid r = 0.48, p = 0.01). These data show that dietary fat given as a bolus can lead to an increase in the proliferation of human colonic cells, possibly as a consequence of raised levels of cytotoxic acidic lipids in the faecal stream.